Heavy metal accumulation in leafy vegetables grown in industrial areas under varying levels of pollution (Bangladesh Journal of Agricultural Research, 2018)
The concentration of lead (Pb), cadmium (Cd), nickel (Ni), cobalt (Co) and chromium (Cr) in three popular leafy vegetables such as spinach (Spinacia oleracea), red amaranth (Amaranthus tricolor) and amaranth (Amaranthus oleraseus) and that in the respective soils were assessed. These crops and soils were collected from two industrial areas (Kalakoir and Zorun, Konabari, Gazipur), and one non-industrial area (Bangladesh Agricultural Research Institute-BARI) under Gazipur district. The concentration of heavy metal in different parts of plant followed the roots>leaves>stem and in soils the order was Kalakoir (pollution)> Zorun (medium pollution) > BARI (low/non-pollution). In all three leafy vegetables similar trend of metal contents was observed i.e. Ni>Cr>Pb>Co>Cd. In the highly pollution area (Kalakoir) the Pb and Ni concentration was found in the order of amaranth>spinach>red amaranth. The Cd concentration was in the order of spinach>amaranth>red amaranth whereas for Cd it was amaranth>red amaranth>spinach and for Cr it was red amaranth>amaranth>spinach. The Pb, Cd, Ni, Co and Cr concentrations in the studied vegetables grown in the low polluted area were below the maximum acceptable levels proposed by the Joint FAO/WHO Expert Committee on Food Additives, except, Cd in spinach and amaranth. However, the higher concentrations of Pb, Cd, Ni, Co and Cr in vegetables grown in the industrial areas indicates that industrial discharge causes heavy metals contamination of soil and eventually their accumulation in plants.Bangladesh J. Agril. Res. 43(1): 39-51, March 2018